Volume 6: Structures and Dynamics, Parts a and B 2011
DOI: 10.1115/gt2011-45829
|View full text |Cite
|
Sign up to set email alerts
|

Rotordynamic Evaluation of Centrifugal Compressor Using Electromagnetic Exciter

Abstract: Since heavier gases exert larger effects on rotordynamic stability, stability evaluation is important in developing or designing high-pressure compressors. To evaluate the rotor stability during operation, an excitation test using a magnetic bearing is the most practical method. In stability analysis, labyrinth seals can produce significant cross-coupling forces, which particularly reduce the damping ratio of the first forward mode. Therefore, forward modes should be distinguished from backward modes in the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…A high-pressure centrifugal compressor [11] was used to test the effect of the damper seal in a full-scale machine. The Table 2 Conditions for CFD analysis point with carbon dioxide gas operation, the outlet pressure is 19.6 MPa (abs) for an inlet pressure of 6.08 MPa (abs).…”
Section: Overview Of the High-pressure Centrifugal Compressor Testmentioning
confidence: 99%
“…A high-pressure centrifugal compressor [11] was used to test the effect of the damper seal in a full-scale machine. The Table 2 Conditions for CFD analysis point with carbon dioxide gas operation, the outlet pressure is 19.6 MPa (abs) for an inlet pressure of 6.08 MPa (abs).…”
Section: Overview Of the High-pressure Centrifugal Compressor Testmentioning
confidence: 99%
“…Lee [32] introduced a complex number to describe the motion status of the rotor, used the direct frequency response function method to identify parameter, and separated positive and negative frequency precessions. Takahashi et al [33] compared traditional frequency response function recognition with direct frequency response function recognition in the complex field and found that the advantages of recognition with complex field. Although the positive and negative precession can be effectively separated, the model of this method is relatively simple and is only suitable for the occurrence of a single peak in the resonance region.…”
Section: Introductionmentioning
confidence: 99%
“…Rotor stability identification methods for rotor-bearing systems have been investigated by many researchers, and they estimated rotor stability during the shop test based on both frequency and time domain signal analysis [1,2]. Takahashi et al [1], Kocur and Cloud [2], and Pettinato et al [3] did a plenty of work on shop rotor dynamic testing by using the electromagnetic bearing as a shaker to excite the rotor system. Cloud [4] developed the Multiple Output Backward Autoregressive (MOBAR) method for time domain signals and carried out significant work on the rotor stability investigation.…”
Section: Introductionmentioning
confidence: 99%